2016
DOI: 10.1016/j.math.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Can a professional development workshop with follow-up alter practitioner behaviour and outcomes for neck pain patients? A randomised controlled trial

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…After screening of titles and abstracts, 172 studies were assigned for full-text reading; of which only 13 met the eligibility criteria. Of these, 2 references were multiple publications; thus, analysis was conducted on 11 unique studies (six individual RCTs [ 46 51 ] and five cluster RCTs [ 52 56 ]) reported in 13 publications (see Fig. 1 for the Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening of titles and abstracts, 172 studies were assigned for full-text reading; of which only 13 met the eligibility criteria. Of these, 2 references were multiple publications; thus, analysis was conducted on 11 unique studies (six individual RCTs [ 46 51 ] and five cluster RCTs [ 52 56 ]) reported in 13 publications (see Fig. 1 for the Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of the included studies by country of origin was as follows: the Netherlands ( n = 4) [ 49 , 50 , 52 , 55 ], UK ( n = 2) [ 48 , 53 ], Australia (n = 2) [ 51 , 54 ], USA ( n = 1) [ 46 ], Switzerland (n = 1) [ 47 ], and Ireland ( n = 1) [ 56 ]. Targeted MSK disorders included five studies on LBP [ 48 , 52 , 53 , 55 , 56 ], two studies on hip and knee osteoarthritis (OA) [ 49 , 50 ], one on whiplash [ 54 ], two on neck pain [ 46 , 51 ], and one on spinal disorders [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations